Fear of cancer recurrence as a pathway from fatigue to psychological distress in mothers who are breast cancer survivors. (8th July 2022) - Kuswanto, Carissa Nadia; Sharp, Jessica; Stafford, Lesley; Schofield, Penelope
Abstract: Fatigue is prevalent and pervasive among breast cancer survivors. Mothers are particularly susceptible to fatigue due to the ongoing demands of their caring role. While fatigue has been associated with psychological distress in prior research, the pathway by which fatigue translates into psychological distress is unclear. Given the theoretical and empirical links between fatigue, fear of cancer recurrence (FCR) and psychological distress, the role of FCR in mediating the relationship between fatigue and psychological distress in mothers who are breast cancer survivors was investigated. Ninety‐two mothers who were breast cancer survivors completed the Depression, Anxiety and Stress Scale, PROMIS‐Cancer Fatigue Short Form and Concerns About Cancer Recurrence scale in an online survey. Mediation analysis via PROCESS was used to examine whether fatigue predicted depression, anxiety or stress through FCR. Fear of cancer recurrence mediated the relationships between fatigue and anxiety and fatigue and stress, while fatigue directly predicted depression. This study highlights FCR as a potential pathway to anxiety and stress in response to ongoing fatigue, and as a mechanism of action to reduce psychological distress among mothers who are breast cancer survivors. Future research examining this pathway from fatigue to psychological distress should also explore the nature of mothers' fears about their cancer recurring.